Sistem Peminjaman Peralatan Pesta Berbasis Sistem Informasi Geografis - Windy Prigandari Ibrahim; Tajuddin Abdillah; Edi Setiawan (Diffusion: Journal of Systems and Information Technology, 2021)
Party equipment loan service is a place to serve all party-related equipment. It is currently such a secondary need for Gorontalo City and Gorontalo District community when organizing. Certain Party which requires supporting equipment such as frame tent, documentation, cosmetic, and others. Because of lots of service providers, users experience difficulty in choosing the wanted one. In addition, user highly need to have information related to an accurate provider location. Objective of this research was to design a system which a could provide a party equipment loan service by applying GIS technology. The technology was helpful for community to help them find the information associated with the party equipment loan service along with its location.